2010
DOI: 10.1002/jcp.22291
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytes decrease Runx2 expression in osteoblastic cells: Roles of PPARγ and adiponectin

Abstract: The mechanisms through which bone marrow adipocytes might influence differentiation and function of osteoblasts are not completely understood. To investigate the direct effects of bone marrow fat cells on osteoblast function, an ex vivo co-culture system was utilized comprising either primary fat cells or differentiated 3T3-L1 adipocytes and osteoblastic cells on transwells. In co-culture, both adipocytes and osteoblastic cells were differentiated into adipocytes or osteoblasts, respectively, before culturing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 42 publications
2
36
0
Order By: Relevance
“…Some studies have suggested that the presence of adipocytes can influence differentiation of mesenchymal stem cells (MSCs) into adipocytes, thereby inhibiting the differentiation into other cell lines [13]. We and others reported that directly co-culturing bone marrow MSCs with fully differentially adipocytes decreased osteoblast differentiation by decreasing RunX2 mRNA expression [14,15], suggesting that these cells are metabolically active but negatively regulate differentiation of MSCs into osteoblasts. Recent studies have suggested that, in addition to adipose, liver and muscle tissue, the osteoblast is also an important target tissue for insulin action [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that the presence of adipocytes can influence differentiation of mesenchymal stem cells (MSCs) into adipocytes, thereby inhibiting the differentiation into other cell lines [13]. We and others reported that directly co-culturing bone marrow MSCs with fully differentially adipocytes decreased osteoblast differentiation by decreasing RunX2 mRNA expression [14,15], suggesting that these cells are metabolically active but negatively regulate differentiation of MSCs into osteoblasts. Recent studies have suggested that, in addition to adipose, liver and muscle tissue, the osteoblast is also an important target tissue for insulin action [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The reciprocal relationship between bone adiposity and bone mineral density has long been recognized. PPARγ is a prime regulator of adipogenesis and as such, the activation of PPARγ in precursors of nonadipogenic lineage cells triggers their transdifferentiation into adipocytes and shifts the bone marrow cell fate decision towards the adipogenesis 4,26,30. However, the effects of PPARγ in ligands on the differentiation of cultured osteoprogenitor cells remain controversial 10-12.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that PPARγ activity directly inhibits osteogenesis by diverting mesenchymal stem cells from the osteogenic phenotype to the adipogenic lineage. This shift in mesenchymal stem cell differentiation to favor the adipocyte lineage over the osteoblast lineage directly contributes to imbalances in bone formation and resorption, and ultimately leads to bone loss 8,10,17,18.…”
Section: Discussionmentioning
confidence: 99%